Proline accumulation and metabolism-related genes expression profiles in Kosteletzkya virginica seedlings under salt stress - Wang, Hongyan; Tang, Xiaoli; Wang, Honglei; Shao, Hong-Bo (Frontiers in Plant Science, 2015)
Proline accumulation is a common response to salt stress in many plants. Salt stress also increased proline concentration in roots, stems and leaves of Kosteletzkya virginica seedling treated with 300mM NaCl for 24h and reached 3.75, 4.76 and 6.83 fold higher than controls. Further study on proline content in leaves under salt stress showed that proline content increased with increasing NaCl concentrations or time. The proline level peaked at 300 mM NaCl for 24h and reached more than 6-fold higher than control, but at 400mM NaCl for 24h proline content fell back slightly along with wilting symptom. To explore the cause behind proline accumulation, we first cloned full length genes related to proline metabolism including KvP5CS1, KvOAT, KvPDH, KvProT from Kosteletzkya virginica and investigated their expression profiles. The results revealed that the expressions of KvP5CS1 and KvProT were sharply up-regulated by salt stress and the expression of KvOAT showed a slight increase with increasing salt concentrations or time, while the expression of KvPDH was not changed much and slightly decreased before 12h and then returned to the original level. As the key enzyme genes for proline biosynthesis, the up-regulated expression of KvP5CS1 played a more important role than KvOAT for proline accumulation in leaves under salt stress. The low expression of KvPDH for proline catabolism also made a contribution to proline accumulation before 12h.